2006
DOI: 10.1007/s00209-005-0892-8
|View full text |Cite
|
Sign up to set email alerts
|

Ozsváth-Szabó invariants and fillability of contact structures

Abstract: Abstract. Recently Ozsváth and Szabó defined an invariant of contact structures with values in the Heegaard-Floer homology groups. They also proved that a version of the invariant with twisted coefficients is non trivial for weakly symplectically fillable contact structures. In this article we show that their non vanishing result does not hold in general for the contact invariant with untwisted coefficients. As a consequence of this fact Heegaard-Floer theory can distinguish between weakly and strongly symplec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 16 publications
1
58
0
Order By: Relevance
“…This fact raised the hope that these invariants could be non trivial for any tight contact structure. However in [6] we showed that the untwisted contact invariant reduced modulo 2 can vanish even for weakly symplectically fillable contact structures. Those examples however left open the question whether the twisted invariants were non trivial for every tight contact structures.…”
Section: Introductionmentioning
confidence: 92%
“…This fact raised the hope that these invariants could be non trivial for any tight contact structure. However in [6] we showed that the untwisted contact invariant reduced modulo 2 can vanish even for weakly symplectically fillable contact structures. Those examples however left open the question whether the twisted invariants were non trivial for every tight contact structures.…”
Section: Introductionmentioning
confidence: 92%
“…If no such cover of the base exists (and V is not a Lens space) then its base B is a sphere with exceptional points of order (2, 2, n), (2,3,3), (2,3,4) or (2, 3, 5) (see [31,Theorem 13.3.6]). In each case B is covered by S 2 and all curves in the regular locus of B bounds a disk whose pre-image in S 2 is disconnected so ξ is virtually overtwisted according to [7, Proposition 4.1 and Lemma 4.7].…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…Honda, Kazez, and Matić have since shown this to be the case for all such open books [7], [9], [8]. However, the precise relationship between c(ξ) and the tightness of ξ is still unknown -there are tight contact structures with vanishing contact invariant [4]. In fact, Ghiggini, Honda, and Van Horn-Morris recently showed that the contact invariant vanishes for contact structures with positive Giroux torsion [5].…”
Section: Introductionmentioning
confidence: 99%